Characteristics of work-related movements and essential physical attributes of a specialist in adaptive physical education - Kielevyaynen L.M.; Babaytseva V.A. (Theory and Practice of Physical Culture, 2025)
Objective of the study was to characteristics of labor activities and the physical attributes that are essential for a specialist in adaptive physical education. Methods and structure of the study. The research was conducted at Petrozavodsk State University for a period of three years. The sample consisted of 40 fourth-year students aged 20 to 22, pursuing a degree in 49.03.02 «Physical Education for People with Disabilities». All participants completed a practical, professionally-oriented internship, which lasted three months, at residential schools and the rehabilitation center of the Children’s City Hospital. Results and conclusions. The unique characteristics of the work and the essential physical attributes of an APC professional are explored. The authors suggest that the practical exercises in the course «Physical Culture and Sport (Elective)» for students of the course «Physical Culture for People with Disabilities» should include activities that involve measuring distances, distinguishing between muscle efforts, altering the pace and direction of movement, and enhancing speed.